Al-áº’awÄhir Al-á¹¢autiyah fi Qiá¹£á¹£ah â€œSafÄ«nah Al-NÅ«hâ€ li Ahmad SyauqÄ« (DirÄsah TahlÄ«liyah UslÅ«biyah) - Alif Cahya Setiyadi; Abdul Hafidz Zaid; Tyas Pradhita Astari (Arabic Education Program IAIN Pekalongan, 2020)
This article aims to examine the poetry of Noah's ark by Ahmad Syauqi from aspects of sound or patterns. As one of the phenomenal works in the history of The Arabic fiction genre, this genre of poetry has the main characteristics in terms of the use and selection of special rhythms that are able to influence the imagination of readers or listeners so as to build their own perception of thinking. This article focuses on exploring the characteristics of sound patterns descriptively with modern literary analysis methods. From the analysis of sound patterns, it is concluded that there are basic rhythms and metrums in the study of modern literary sounds of this phenomenal poem. There are two variants of fundamental rhythms, namely internal and external rhythms. The external rhythm is manifested in the form of al-wazn from poetry which includes two main types namely bahr kÄmil and bahr rajzi, the structure of the rhythm used, and the form of poetry. On the other hand, the poem also uses internal rhythms by giving rise to the rhetorical beauty (al-binyah al-badi'iyah) which consists largely of al-jinÄs and al-á¹ibÄq.